PELATIHAN MEMBUAT KESET DARI BAJU KAOS BEKAS DI SLB YP3LB SUDIANG MAKASSAR - Bastiana; Kasmawati, St.; Meidina, Tatiana; Sulasminah, Dwiyatmi; Julinda; Nurkhotimah, Anis; Salmawati (Transpublika Publisher, 2023)
Doormat-making training can be an effective way to increase the independence of children with special needs. In this training, children are taught how to make mats using simple materials such as old t-shirts, wire, scissors, and sticks or chopsticks. The method used to train students with special needs to make mats from used t-shirts involves identifying their existing level of knowledge and skills, conducting training, and evaluating the training activities. The training in making mats from used t-shirts can be carried out and runs as expected. Students can follow the steps in making a mat, although it may require more time and patience from the trainer in guiding them.